Journalism, democracy and politics. Reconsiderations on press freedom: Reconsideraciones sobre la libertad de prensa - Bonilla Vélez, Jorge Iván (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
This article presents the results of a study that described some of the challenges facing press freedom and the exercise of journalism in Latin America and the advances in this area have been carried out. It also aims to problematize some of the hegemonic notions of “press freedom”, and from there to observe the role of state and citizenship in the areas of empowerment of democratic communicative exchange as other possible routes to rethink the press freedom.